Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Ask your questions and receive precise answers from experienced professionals across different disciplines. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To find the fifteenth term of the given geometric sequence [tex]\( -\sqrt{5}, \sqrt{10}, -2\sqrt{5}, \ldots \)[/tex]:
1. Identify the first term ([tex]\(a_1\)[/tex]) of the sequence:
[tex]\[ a_1 = -\sqrt{5} \][/tex]
2. Identify the second term ([tex]\(a_2\)[/tex]) of the sequence:
[tex]\[ a_2 = \sqrt{10} \][/tex]
3. Identify the third term ([tex]\(a_3\)[/tex]) of the sequence:
[tex]\[ a_3 = -2\sqrt{5} \][/tex]
4. Calculate the common ratio ([tex]\(r\)[/tex]) of the sequence using the first two terms:
[tex]\[ r = \frac{a_2}{a_1} = \frac{\sqrt{10}}{-\sqrt{5}} \][/tex]
Simplify the fraction:
[tex]\[ \frac{\sqrt{10}}{-\sqrt{5}} = \frac{\sqrt{2} \cdot \sqrt{5}}{-\sqrt{5}} = \sqrt{2} \cdot \frac{\sqrt{5}}{\sqrt{5}} = \sqrt{2} \cdot (-1) = -\sqrt{2} \][/tex]
So, the common ratio [tex]\(r\)[/tex] is:
[tex]\[ r = -\sqrt{2} \][/tex]
5. Use the formula for the [tex]\(n\)[/tex]-th term of a geometric sequence to find the fifteenth term ([tex]\(a_{15}\)[/tex]):
[tex]\[ a_n = a_1 \cdot r^{n-1} \][/tex]
For the fifteenth term ([tex]\(n = 15\)[/tex]):
[tex]\[ a_{15} = a_1 \cdot r^{15-1} = a_1 \cdot r^{14} \][/tex]
Substituting the known values:
[tex]\[ a_{15} = -\sqrt{5} \cdot (-\sqrt{2})^{14} \][/tex]
6. Simplify [tex]\((- \sqrt{2})^{14}\)[/tex]:
Since the exponent is even, the negative sign will be squared out, and we can write:
[tex]\[ (-\sqrt{2})^{14} = (\sqrt{2})^{14} \][/tex]
Calculate [tex]\((\sqrt{2})^{14}\)[/tex]:
[tex]\[ (\sqrt{2})^{14} = (2^{1/2})^{14} = 2^{7} = 128 \][/tex]
7. Combine the terms to find [tex]\(a_{15}\)[/tex]:
[tex]\[ a_{15} = -\sqrt{5} \cdot 128 = -128\sqrt{5} \][/tex]
Therefore, the fifteenth term of the sequence is:
[tex]\[ \boxed{-128 \sqrt{5}} \][/tex]
1. Identify the first term ([tex]\(a_1\)[/tex]) of the sequence:
[tex]\[ a_1 = -\sqrt{5} \][/tex]
2. Identify the second term ([tex]\(a_2\)[/tex]) of the sequence:
[tex]\[ a_2 = \sqrt{10} \][/tex]
3. Identify the third term ([tex]\(a_3\)[/tex]) of the sequence:
[tex]\[ a_3 = -2\sqrt{5} \][/tex]
4. Calculate the common ratio ([tex]\(r\)[/tex]) of the sequence using the first two terms:
[tex]\[ r = \frac{a_2}{a_1} = \frac{\sqrt{10}}{-\sqrt{5}} \][/tex]
Simplify the fraction:
[tex]\[ \frac{\sqrt{10}}{-\sqrt{5}} = \frac{\sqrt{2} \cdot \sqrt{5}}{-\sqrt{5}} = \sqrt{2} \cdot \frac{\sqrt{5}}{\sqrt{5}} = \sqrt{2} \cdot (-1) = -\sqrt{2} \][/tex]
So, the common ratio [tex]\(r\)[/tex] is:
[tex]\[ r = -\sqrt{2} \][/tex]
5. Use the formula for the [tex]\(n\)[/tex]-th term of a geometric sequence to find the fifteenth term ([tex]\(a_{15}\)[/tex]):
[tex]\[ a_n = a_1 \cdot r^{n-1} \][/tex]
For the fifteenth term ([tex]\(n = 15\)[/tex]):
[tex]\[ a_{15} = a_1 \cdot r^{15-1} = a_1 \cdot r^{14} \][/tex]
Substituting the known values:
[tex]\[ a_{15} = -\sqrt{5} \cdot (-\sqrt{2})^{14} \][/tex]
6. Simplify [tex]\((- \sqrt{2})^{14}\)[/tex]:
Since the exponent is even, the negative sign will be squared out, and we can write:
[tex]\[ (-\sqrt{2})^{14} = (\sqrt{2})^{14} \][/tex]
Calculate [tex]\((\sqrt{2})^{14}\)[/tex]:
[tex]\[ (\sqrt{2})^{14} = (2^{1/2})^{14} = 2^{7} = 128 \][/tex]
7. Combine the terms to find [tex]\(a_{15}\)[/tex]:
[tex]\[ a_{15} = -\sqrt{5} \cdot 128 = -128\sqrt{5} \][/tex]
Therefore, the fifteenth term of the sequence is:
[tex]\[ \boxed{-128 \sqrt{5}} \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.